EXPLORING MATHEMATICAL CONCEPTS IN THE LEGACY OF THE BANTEN SULTANATE - Syahla Icha Meta Amelia; Sugiarti Rahmah Kurnia; Maifalinda Fatra (Prima: Jurnal Pendidikan Matematika, 2026)
Mathematics is a form of knowledge that is closely related to everyday life. Although many mathematical concepts are inherently connected to daily experiences, students’ understanding of the material still often encounters various difficulties, particularly in topics such as geometry, graphs of linear equations, and quadratic functions. Based on this understanding, this study aims to identify the functions, symbolic meanings, and mathematical concepts found in Genta, Tengkuluk, and Panji, as well as how this knowledge can be utilized in ethnomathematics-based learning and local wisdom values as an effort to enrich contextual learning resources that are rooted in culture. This research employs a qualitative descriptive approach. The research subjects consist of two curators from the National Museum of Indonesia and one religious expert from the Banten community. Data were collected using instruments comprising observation sheets, interview guidelines, and documentation. The data were analyzed using the qualitative data analysis process proposed by Miles and Huberman. The data reduction process was carried out by simplifying the results of interviews, observations, and documentation according to aspects related to mathematical concepts as well as religious and cultural values found in the heritage of the Banten Sultanate. The data were then presented visually in the form of photographs, tables, and narrative descriptions illustrating the relationships between heritage objects, mathematical concepts, and cultural and religious values. The final stage involved drawing conclusions from the research findings. Overall, the findings indicate that the integration of mathematical concepts within cultural artifacts provides meaningful potential for developing contextual and culturally grounded ethnomathematics-based learning resources.